Team, Front cover, Editorial information, Table of Content, Back Cover - Journal Editor (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2015)
Jurnal Sains dan Kesehatan. 2015. Volume 1 Nomor 1. Front cover, Editorial information, Table of Content, Back Cover